Treatment of chronic heel osteomyelitis in vasculopathic patients. Can the combined use of Integra(®), skin graft and negative pressure wound therapy be considered a valid therapeutic approach after partial tangential calcanectomy? - Fraccalvieri, Marco (Int Wound J, 2011)
Osteomyelitis of the calcaneus is a difficult problem to manage. Patients affected by osteomyelitis of the calcaneus often have a below‐the‐knee amputation because of their comorbidity. In this article, we present seven cases of heel ulcerations with chronic osteomyelitis treated with Integra(®) Dermal Regeneration Template, skin graft and negative pressure wound therapy after partial tangential calcanectomy, discussing the surgical and functional results. In this casuistic of patients, all wounds healed after skin grating of the neodermis generated by Integra(®), with no patient requiring a below‐knee amputation.